PEMANFAATAN PLTS 10 kWp TERPASANG UNTUK CATU DAYA POMPA AIR DI DESA BAN KARANGASEM - Patandean, Awgustus; Giriantari, I A Dwi; Ariastina, Wayan Gede (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
There are 19 banjars considered as custom And 16 official banjars at Ban Village located in the Regency of Karangasem Bali. The people in Ban, especially who live at the village of Tempek Asti and the village of Manik Aji, have troubles to get the ccess of fresh water. As the result, they must take a longdistance walk and the condition is teribly dangerous. The village of Manik Aji has off-grid system powered by PLTS 10 kWp which was built in 2017 by the minister of source and energy of Indonesian Republic. It had done by Manpower Department and ESDM of Bali Province. In 2021, PLN (Indonesian Electric state) had designed to supply the electricity at Manik Aji village. Therefore,the installed PLTS was functioned as the source of electric support to fulfill the society's needs of tempek Asti Manik aji village. The water pump type is AC submersible Kepeida 4SMP3 26-2,2 kWp and 2.093,14 Wh of energy. The total head is 60,005 meter which the power needed 2,2 kWp and 2.093,14 Wh of energy so the water pump can operate for 3,5 hours with the water debit is 3 m3/h producing 10.000 litter of water and has fulfilled the water needs of society at tempek Asti Manik Aji village about 1.200 litter daily.